HAMBATAN PERLEKATAN Salmonella typhi PADA ENTEROSIT TIKUS PUTIH (WISTAR) OLEH ANTIBODI POLIKLONAL ANTI PROTEIN HEMAGLUTININ SUB UNIT PILLI - Sri Darmawanti (JURNAL LITBANG, 2007)
Typhoid Dengue is a disease coused by Salmonella typhy bacteria, and constitutes a seriotts disea